Cross-Cultural Management and its Issues- An In-depth study of Indian People working in United Kingdom - Gupta, Sachin (2012)
This study examines the problems Indian people face in UK due to the cross-cultural differences and check whether these differences affect their work performance. Further it also identifies how these problems are managed by them. The objective of the study is to make Indian people aware about these problems in advance before they come to UK so that they know how to tackle these problems. This study also reviewed the cultural differences of both the countries. The study followed explanatory approach where explanation about every particular topic is provided and therefore it helps to answer questions such as “How” and “Why” while explaining different situations. The study was depended on quantitative technique for collecting data where a close-ended questionnaire was used to collect the data from 211 Indian who are living in UK.